2006
DOI: 10.1111/j.1939-1676.2006.tb02857.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponins as Indicators of Acute Myocardial Damage in Dogs

Abstract: Cardiac troponin I (cTnI) and T (cTnT) have a high sequence homology across phyla and are sensitive and specific markers of myocardial damage. The purpose of this study was to evaluate the Cardiac Reader, a human point-of-care system for the determination of cTnT and myoglobin, and the Abbott Axsym System for the determination of cTnI and creatine kinase isoenzyme MB (CK-MB) in healthy dogs and in dogs at risk for acute myocardial damage because of gastric dilatationvolvulus (GDV) and blunt chest trauma (BCT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 35 publications
(23 reference statements)
3
20
2
1
Order By: Relevance
“…Although this method does not identify specific isoenzymes or isoforms, it provides an estimate of CK‐MM activity, which is responsible for the majority of plasma CK activity in many species. CK‐MB can be measured by immunoenzymatic methods designed for diagnostic purposes in people with myocardial diseases; these methods have also been used in dogs, although definitive validation studies have not been done 5–7 . By contrast, CK‐BB and macroenzymes can be measured only by more expensive and labor‐intensive methods, such as chromatography, immunoprecipitation, immunoinhibition, differential enzyme activation, and electrophoresis 3 …”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although this method does not identify specific isoenzymes or isoforms, it provides an estimate of CK‐MM activity, which is responsible for the majority of plasma CK activity in many species. CK‐MB can be measured by immunoenzymatic methods designed for diagnostic purposes in people with myocardial diseases; these methods have also been used in dogs, although definitive validation studies have not been done 5–7 . By contrast, CK‐BB and macroenzymes can be measured only by more expensive and labor‐intensive methods, such as chromatography, immunoprecipitation, immunoinhibition, differential enzyme activation, and electrophoresis 3 …”
Section: Introductionsupporting
confidence: 89%
“…The limited information about CK isoenzymes in dogs is focused on CK‐MM and CK‐MB 5–13 . Only one study reported serum CK‐BB activity in dogs with neurologic disease 12 .…”
Section: Introductionmentioning
confidence: 45%
See 1 more Smart Citation
“…Myocardial ischemia secondary to hypoperfusion, reperfusion injury, and oxygen‐free radical production is thought to occur . This has been supported by showing an increase in cardiac troponins in GDV patients . These insults to the myocardium during the disease process may be exacerbating nonclinical underlying heart disease, making it difficult for the patient to compensate.…”
Section: Discussionmentioning
confidence: 99%
“…Genes distinct from those encoding skeletal muscle isoforms encode cardiac troponin I, 27 and this troponin is a marker of myocardial cellular injury. Thus, cardiac troponins are more specific for cardiac damage, compared with the specificity of LDH or CK activity or myoglobin concentration 28–30 . Furthermore, cardiac troponin concentrations are generally not affected by nonspecific types of skeletal muscle damage, including trauma, IM injections, or strenuous exercise.…”
Section: Minimum Database For Neuromuscular Diseasesmentioning
confidence: 99%